Increased risk of new-onset diabetes in patients with COVID-19: a systematic review and meta-analysis - Li, Jiajun; Li, Yapeng; Wang, Zhenzhen; Liu, Nanyang; He, Lanye; Zhang, Han (Frontiers in Public Health, 2023)
Background There is growing evidence that patients with COVID-19 are at increased risk of new-onset diabetes. The limited preliminary studies do not provide strong evidence. To assess the association of the SARS-CoV-2 virus with new-onset diabetes and to characterize the population. Methods Search PubMed, Embase, Cochrane Library, and Web of Science electronic databases for a limited period from December 2019 to July 2022. Two independent reviewers conducted a thorough review of eligible articles and extracted relevant information. Pooled proportions, risk ratios (RR), and 95% confidence intervals (95% CI) indicated the incidence and risk ratios of events. Results The incidence of new-onset diabetes and hyperglycemia in patients with COVID-19 was 5% (P < 0.001) (3 and 30% for new-onset diabetes and hyperglycemia, respectively), with age, ethnicity, time of diagnosis, and study type all having an impact on the incidence (P < 0.05). New-onset diabetes and hyperglycemia were 1.75 times higher in COVID-19 patients than in non-COVID-19 patients. In new-onset diabetes and hyperglycemia population, the percentage of men is 60% (40% for women), with a mortality rate of 17%. The proportion of new-onset diabetes and hyperglycemia after infection with COVID-19 was 25% in men and 14% in women. Conclusions The incidence and relative risk of new-onset diabetes and hyperglycemia are elevated after COVID-19 infection, especially in the early COVID-19 and male populations. Systemic review registration PROSPERO registration no.: CRD42022382989 https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=382989.